Owls - Gregory, Josh (Nature's children (New York, N.Y.), 2013)
With their strange faces and nocturnal habits, owls have long captured the imaginations of people around the world. Readers will discover how these feathered flyers swoop down to snatch prey in their talons, blend in with their environments, and work together to raise their young.